Answer:
k=8
Step-by-step explanation:
Question says that given expression is [tex]\left(x^3\cdot x\right)^2[/tex]
Now we need to rewrite that expression in form of [tex]x^k[/tex].
To do that we need to simplify given problem [tex]\left(x^3\cdot x\right)^2[/tex].
x is same as [tex]x^1[/tex]
[tex]=\left(x^3\cdot x^1\right)^2[/tex]
we can begin with inner parenthesis
[tex]=\left(x^{3+1}\right)^2[/tex]
[tex]=\left(x^{4}\right)^2[/tex]
[tex]=x^{4*2}[/tex]
[tex]=x^8[/tex]
Now compare that with [tex]=x^k[/tex], we get:
k=8
Which is different value that Linda got.
Hence answer of the Linda is wrong.